PEARL CULTURE—ITS POTENTIAL AND IMPLICATIONS IN INDIA - Alagarswami, K; Qasim, S Z (Indian Journal of Fisheries, 2011)
Pearl fisheries of India are of ancient origin. The pearl oyster resources are locatedmainlyin the Gulf of Kutch and Gulf of Mannar. They are subjected to wide fluctuationsfrom year to year, particularly when they are exploited for natural pearls. In 1972,Vei^alodai, near Tuticorin, was selected as a site for conducting experiments on pearloyster farming and on the development of cultured pearls. Modem method of raft culturewas adopted for raising mother oysters. This method proved successful despite the tryingsea conditions prevailing during the monsoon months. The survival rate of thepearl oysters in the farm was about 78 % during the first year. The oysters grew fast in thefarm in certain seasons and remained healthy throughout the experiments. Fouling bydifferent organisms was a serious problem and, if not checked properly, led to mortalityof oysters. Settlement of the spats of pearl oyster occurred at the farm from May to July.At Veppalodai, the techniques of producing cultured pearls from the Indian pearloyster, Pittctada fucata, were developed and for the first time free, spherical culturedpearls were produced. The potential and implications of pearl culture in India havebsen discussed in relation to the situations prevailing in the pearl culture industry ofother parts of the world.